A critical appraisal of the quality of guidelines for radiation protection in interventional radiology using the AGREE II tool: A EuroAIM initiative. Issue 143 (October 2021) - Zanardo, Moreno; Gerasia, Roberta; Giovannelli, Lorenzo; Scurto, Giuseppe; Cornacchione, Patrizia; Cozzi, Andrea; Durante, Stefano; Schiaffino, Simone; Monfardini, Lorenzo; Sardanelli, Francesco
Highlights: Eleven guidelines were evaluated with overall acceptable guideline quality. Future guidelines should improve clinical and technical applicability. A more widespread involvement of all health professionals is desirable. Abstract: Purpose: To systematically review and assess the methodological quality of guidelines for radiation protection in interventional radiology. Materials and methods: On April 15 th, 2021, a systematic search for guidelines on radiation protection in interventional radiology was performed using MEDLINE, EMBASE, National Guideline Clearinghouse, and National Institute for Health and Clinical Excellence databases. Among retrieved guidelines, we then excluded those not primarily focused on radiation protection or on interventional radiology. Authors' professional role and year of publication were recorded for each included guideline. Guideline quality evaluation was performed independently by three authors using the six-domain tool "AGREE II", with an overall guideline quality score divided into three classes: low (<60%), acceptable (60–80%), and good quality (>80%). Results: Our literature search identified 106 citations: after applying exclusion criteria, 11 guidelines published between 2009 and 2018 were included, most of their authors being interventional radiologists (168/224, 75%). Overall quality of included guidelines was acceptable (median 72%, interquartile range 64–83%), with only one guideline (9%) with overall low quality and four guidelines (36%) with overall good quality. Among AGREE II domains, "Scope and Purpose", "Clarity of Presentations", and "Editorial Independence" had the best results (87%, 76%, and 75% respectively), while "Applicability", "Rigor of Development", and "Stakeholder Involvement" the worst (46%, 49%, and 52% respectively). Conclusion: Considering all guidelines, the overall methodological quality was acceptable with one third of them reaching the highest score class. The "Applicability" domain had the lowest median score, highlighting a practical implementation gap to be addressed by future guidelines.